2003
DOI: 10.1051/0004-6361:20031024
|View full text |Cite
|
Sign up to set email alerts
|

XMM-Newton observations of the nitrogen-rich Wolf-Rayet star WR 1

Abstract: Abstract. We present XMM-Newton results for the X-ray spectrum from the N-rich Wolf-Rayet (WR) star WR 1. The EPIC instrument was used to obtain a medium-resolution spectrum. The following features characterize this spectrum: (a) significant emission "bumps" appear that are coincident with the wavelengths of typical strong lines, such as Mg, Si, and S; (b) little emission is detected above 4 keV, in contrast to recent reports of a hard component in the stars WR 6 and WR 110 which are of similar subtype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 37 publications
3
31
0
Order By: Relevance
“…However, observations show the contrary-the handful of single WR stars with available spectral measurements all show X-ray emission harder than typically found in O stars (Skinner et al 2002a(Skinner et al , 2002bIgnace et al 2003). This trend is confirmed by our new data on WR 142.…”
Section: X-ray Emission From a Wo-type Star L47supporting
confidence: 82%
See 1 more Smart Citation
“…However, observations show the contrary-the handful of single WR stars with available spectral measurements all show X-ray emission harder than typically found in O stars (Skinner et al 2002a(Skinner et al , 2002bIgnace et al 2003). This trend is confirmed by our new data on WR 142.…”
Section: X-ray Emission From a Wo-type Star L47supporting
confidence: 82%
“…Observations with the XMM-Newton and Chandra X-ray telescopes established that some bona fide single WN stars are X-ray active (Skinner et al 2002a(Skinner et al , 2002bIgnace et al 2003;Oskinova 2005), while others are apparently not (Oskinova 2005;Gosset et al 2005). Oskinova et al (2003) found that no single WC star had been conclusively detected at X-ray energies, a result that continues to hold.…”
Section: Introductionmentioning
confidence: 99%
“…Although the star is detected, the hot component seems to be absent or at least comparatively much cooler. Ignace et al (2003) also tentatively reported the detection in the X-ray spectrum of absorption features, interpreted as being due to K-shell absorption edges of N and Si. They argued that WR 1 is probably single contrary to WR 6 and WR 110.…”
Section: Send Offprint Requests To: E Gossetmentioning
confidence: 79%
“…Markedly puzzling in this respect is the observation of WR 1 (WN4) by Ignace et al (2003) who suspect that the Model B (1.2 keV) Model C (WR 25) hot component is absent in WR 1; they further argue that it could be the first example of an X-ray emission generated by a single WR star: a soft intrinsic emission due to shocks resulting from hydrodynamical instabilities in the wind. However, the observed count rates for WR 1 are still a factor 100 larger than our secure limit on WR 40.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation